2013
DOI: 10.1002/emmm.201302859
|View full text |Cite
|
Sign up to set email alerts
|

Effective gene therapy for haemophilic mice with pathogenic factor IX antibodies

Abstract: Formation of pathogenic antibodies is a major problem in replacement therapies for inherited protein deficiencies. For example, antibodies to coagulation factors (‘inhibitors’) seriously complicate treatment of haemophilia. While immune tolerance induction (ITI) protocols have been developed, inhibitors against factor IX (FIX) are difficult to eradicate due to anaphylactic reactions and nephrotic syndrome and thus substantially elevate risks for morbidity and mortality. However, hepatic gene transfer with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
153
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(157 citation statements)
references
References 65 publications
3
153
0
1
Order By: Relevance
“…in hemophilia B) and where enzyme replacement treatment often induces inhibitory antibodies to the protein. It has been shown that strong hepatocyte-specific transgene expression, whilst circumventing either the transduction of, or expression in, APCs, can also prevent and even abrogate the formation of such inhibitors [77,78]. …”
Section: A Brief History Of In-vivo Gene Therapymentioning
confidence: 99%
“…in hemophilia B) and where enzyme replacement treatment often induces inhibitory antibodies to the protein. It has been shown that strong hepatocyte-specific transgene expression, whilst circumventing either the transduction of, or expression in, APCs, can also prevent and even abrogate the formation of such inhibitors [77,78]. …”
Section: A Brief History Of In-vivo Gene Therapymentioning
confidence: 99%
“…At low vector doses (1 3 10 9 vg per mouse), 1 animal treated with standard AAV8-hF.IX developed an anti-hF.IX transgene antibody (supplemental Figure 6B), whereas none of the animals treated with exo-AAV8 vectors developed antitransgene antibodies (supplemental Figure 6). Accordingly, as previous studies showed that high expression levels promote better transgene-specific immune tolerance, 27,28 we evaluated the frequency of CD4 1 CD25 1 FoxP3 1 regulatory T cells (Tregs) in animals treated with exo-or standard AAV-hF.IX vectors at a dose of 1 3 10 9 vg per mouse. At this dose, no differences were noted in the spleens, however, a significant enhancement in the frequency of Tregs was noticeable in the lymph nodes of exo-AAV-treated animals.…”
Section: Exo-aav Vectors Drive Widespread Enhanced Targeting Of Hepatmentioning
confidence: 99%
“…Support for this therapeutic approach has been shown in the murine hemophilia B model in which liver-directed gene transfer using either adenoassociated viral vectors or lentiviral vectors can reverse preexisting anti-fIX high-titer inhibitors via T-regulatory cell induction. 56,57 In a canine hemophilia A model, liver-directed gene therapy led to tolerance in 3 of 4 dogs. 58 In addition, transplantation of hematopoietic stem cells engineered to express fVIII has been shown to induce fVIII-specific tolerance and eradicated fVIII inhibitors in mouse models.…”
Section: Gene Therapy To Promote Immune Tolerancementioning
confidence: 99%